A Disruptive Influence? "Prevent‐ing" Problems and Countering Violent Extremism Policy in Practice. Issue 2 (June 2017) - Innes, Martin; Roberts, Colin; Lowe, Trudy
Abstract : This article describes how disrupting the activities of suspected violent extremists has become an increasingly significant construct in the policy and practice of the Prevent strand of UK Counter‐Terrorism. Informed by empirical data collected during semi‐structured interviews with police officers involved in conducting disruptions and members of the communities where these occurred, blended with a limited amount of field observation, the analysis documents how and why a logic of disruption has assumed increasing prominence in counter terrorism work. In respect of police interventions in particular, implementing disruptions, rather than pursuing fully‐fledged prosecutions, represents a pragmatic way of reconciling increasing demand with limited resources, as well as managing some of the difficulties of translating intelligence into legal evidence. Conceptualized in this way, the analysis positions disruption as a distinctive mode of crime prevention; one premised upon logics of near‐event interdiction. As such, it is understood as rather different in its operations and functions to other forms of "early intervention" that are increasingly prominent in much contemporary crime prevention policy. By focusing upon how specific Prevent interventions are implemented and performed this analysis makes a particular contribution to our knowledge of counter terrorism work. This reflects the fact that most previous studies of Prevent and other countering violent extremism programs have provided analyses of community perceptions and reactions to policing and the policy frame, rather than the configuration of the interventions themselves.